2022
DOI: 10.3390/agronomy12040812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Fertilization on Yield of Chipping Potato Grown on High Legacy Phosphorus Soil

Abstract: Potato (Solanum tuberosum L.) has low phosphorus (P) use efficiency as compared with other vegetable crops. This study was conducted at two commercial chipping potato farms (A and B) in Northeast Florida to evaluate different P rates for potato production. Plot size was 0.62 and 0.49 hectares for Farms A and B, respectively. The total trial area was 13.32 hectares per growing season for three consecutive years from 2018 to 2020. The randomized complete block design (RCBD) was employed with four replications pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Subsequently, GNPS and TGW also increased. Qiu et al [58] also indicated that minimizing phosphorus fixation and improving phosphorus utilization efficiency was a new scheme to apply phosphorus fertilizer with post-plant applications rather than pre-plant applications.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, GNPS and TGW also increased. Qiu et al [58] also indicated that minimizing phosphorus fixation and improving phosphorus utilization efficiency was a new scheme to apply phosphorus fertilizer with post-plant applications rather than pre-plant applications.…”
Section: Discussionmentioning
confidence: 99%